2021
DOI: 10.1016/j.amj.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Retrospective Analysis of Out-of-Hospital Pediatric Cardiopulmonary Resuscitation Treated by Helicopter Emergency Medical Service in the Netherlands

Abstract: There is generally limited but conflicting literature on the incidence, causes, and outcomes of pediatric out-of-hospital cardiac arrest. This study was performed to determine the incidence and outcome of pediatric out-of-hospital cardiac arrest reported by all helicopter emergency medical services in the Netherlands and to provide a description of causes and treatments and, in particular, a description of the specific interventions that can be performed by a physician-staffed helicopter emergency medical serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The EMS policies for resuscitating and transporting these children have not changed over the study period. Our corrected incidence is similar to Victoria, Australia (4.9/100,000, period: 2000–2016), 10 higher than The Netherlands (3.5/100,000, period: 2015–17), 11 and lower than a North American cohort (8.3/100,00, period: 2007–12). 1 The Dutch study included traumatic POHCA and may have missed some cases and the North American study included patients who did not receive resuscitation efforts by Emergency Medical Services (EMS) and reflected 11 subregions of North America, including 2 urban Southern Ontario regions.…”
Section: Discussionsupporting
confidence: 67%
“…The EMS policies for resuscitating and transporting these children have not changed over the study period. Our corrected incidence is similar to Victoria, Australia (4.9/100,000, period: 2000–2016), 10 higher than The Netherlands (3.5/100,000, period: 2015–17), 11 and lower than a North American cohort (8.3/100,00, period: 2007–12). 1 The Dutch study included traumatic POHCA and may have missed some cases and the North American study included patients who did not receive resuscitation efforts by Emergency Medical Services (EMS) and reflected 11 subregions of North America, including 2 urban Southern Ontario regions.…”
Section: Discussionsupporting
confidence: 67%
“…The available body of evidence focusing on physician-staffed HEMS mainly constitutes data on traumatic injuries, paediatric emergencies, cardiac arrests, or winch operations. [22][23][24][25][26][27] The drowning population treated by the Danish Air Ambulance had a median age of 50 years with a bimodal pattern concentrating on ages one to six and beyond 60 years. For the paediatric subpopulation below six years, the 30-day survival was 75% compared to only 22.7% in the elderly individuals above 65 years.…”
Section: Results Compared To the Existing Literaturementioning
confidence: 99%
“…There was no signi cant difference in total mission or response time between fatal and non-fatal drowning missions. The Danish Air Ambulance spent signi cantly more time providing medical care on-scene in the group with a fatal outcome (median [IQR] 28 [21][22][23][24][25][26][27][28][29][30][31][32] minutes vs 19 [16-29] minutes, p = 0.01). Legend: Information on 30-day follow-up was missing for 16 patients who survived prehospital due to missing CPR number.…”
Section: Operational Data From the Danish Air Ambulancementioning
confidence: 99%
“…Various epidemiologic studies investigated the causes of pre-hospital cardiac arrest in children and showed age-dependent risks exist: While infants die from sudden infant death syndrome, toddlers and small children are at risk for severe respiratory failure and upper airway obstruction. With increasing age, the risk for major trauma events raises ( 15 17 ). The patients in the presented cohort offered various causes for cardiac arrest, which are explainable given the extensive age range and the heterogeneity of the underlying diseases.…”
Section: Discussionmentioning
confidence: 99%